2016
DOI: 10.1590/0074-02760160074
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modeling of cutaneous leishmaniasis in the Andean region of Colombia

Abstract: The objective of this research was to identify environmental risk factors for cutaneous leishmaniasis (CL) in Colombia and map high-risk municipalities. The study area was the Colombian Andean region, comprising 715 rural and urban municipalities. We used 10 years of CL surveillance: 2000-2009. We used spatial-temporal analysis - conditional autoregressive Poisson random effects modelling - in a Bayesian framework to model the dependence of municipality-level incidence on land use, climate, elevation and popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(45 reference statements)
1
20
0
1
Order By: Relevance
“…In the Amazon, an overwhelming number of sandflies are reported in forest areas compared to the peridomiciliary environment, with predominance of Nyssomyia umbratilis, the main vector for Leishmania guyanensis, responsible for the majority of ACL cases in the state [29]. The hypotheses previously reported can be confirmed from the findings of P erez-Fl orez et al (2016) [30] who described a positive association between the forest area coverage and the disease in Colombia, a country bordering Amazonas state. Ocampo et al (2012) [31] also reported a negative correlation between abundance of sandflies in the intra and peridomiciliary environments and the distance of houses from dense vegetation, suggesting that these insects need the forest as a place for resting and reproduction.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the Amazon, an overwhelming number of sandflies are reported in forest areas compared to the peridomiciliary environment, with predominance of Nyssomyia umbratilis, the main vector for Leishmania guyanensis, responsible for the majority of ACL cases in the state [29]. The hypotheses previously reported can be confirmed from the findings of P erez-Fl orez et al (2016) [30] who described a positive association between the forest area coverage and the disease in Colombia, a country bordering Amazonas state. Ocampo et al (2012) [31] also reported a negative correlation between abundance of sandflies in the intra and peridomiciliary environments and the distance of houses from dense vegetation, suggesting that these insects need the forest as a place for resting and reproduction.…”
Section: Discussionmentioning
confidence: 66%
“…The hypotheses previously reported can be confirmed from the findings of Pérez‐Flórez et al . (2016) who described a positive association between the forest area coverage and the disease in Colombia, a country bordering Amazonas state. Ocampo et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results of hot-spot detection and spatiotemporal clustering patterns might offer some useful information to epidemiologists for the control of and to predict VL spread over critical hot-spot areas rather than in an entire region. Multiple causes are possible for the outbreaks of VL, and many previous studies have demonstrated that VL is highly sensitive to environmental factors and that climate affects the spatial and temporal distribution of the disease [15]. For instance, environmental factors, including forest cover, soil type, soil moisture, deforestation, and climate determinants, all play important roles in affecting the distribution of VL transmission [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…One approach to infectious disease modeling is to use these factors to predict transmission and model the data in both space and time. This has been used successfully to estimate the incidence of malaria during eradication campaigns in Namibia and cutaneous leishmaniasis in high-risk areas of Columbia [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%